Adaptasi Family Caregivers dalam Merawat Pasien di Rumah Selama Masa Pandemi COVID-19 - Sri Rahayu; Iis Sapitri (Jurnal Abdimas Kesehatan (JAK), 2022)
The COVID-19 pandemic has changed the way of life of many people, especially in the patients’ care. This also happens to family caregivers who take care of patients at home. Caring for the patient at home is not easy and requires more attention to maintain the patients’ health condition and prevent from the COVID-19. Thus, necessary to give information about the adaptation of family caregivers in caring for patients at home during the COVID-19 pandemic. Outcome Family caregivers can adapt in caring for patients at home. Activities are carried out offline and online using a Poster, PowerPoint, and Zoom Meeting applications with a total of 28 participants. Characteristics of family caregivers are the average age of 35.89±16.48 years with a minimum age of 17 years old and a maximum age of 73 years old. Most of them are women are 18 people (64.29%), 16 people unemployed (57.14%), and 12 people who live in Jakarta (42.86%). Most of the participants who answered correctly about the adaptation of family caregivers during the COVID-19 pandemic were 22 people (78.57%). Knowledge of the participants (family caregivers), have good knowledge in caring for patients at home, but need to be followed up and monitored continuously by cadres or stakeholders from each region.